Quorum Sensing of Periodontal Pathogens - Darije Plančak; Larisa Musić; Ivan Puhar (University of Zagreb. School of Dental Medicine, 2015)
The term 'quorum sensing' describes intercellular bacterial communication which regulates bacterial gene expression according to population cell density. Bacteria produce and secrete small molecules, named autoinducers, into the intercellular space. The concentration of these molecules increases as a function of population cell density. Once the concentration of the stimulatory threshold is reached, alteration in gene expression occurs. Gram-positive and Gram-negative bacteria possess different types of quorum sensing systems. Canonical LuxI/R-type/acyl homoserine lactone mediated quorum sensing system is the best studied quorum sensing circuit and is described in Gram-negative bacteria which employ it for inter-species communication mostly. Grampositive bacteria possess a peptide-mediated quorum sensing system. Bacteria can communicate within their own species (intra-species) but also between species (inter-species), for which they employ an autoinducer-2 quorum sensing system which is called the universal language of the bacteria. Periodontal pathogenic bacteria possess AI-2 quorum sensing systems. It is known that they use it for regulation of biofilm formation, iron uptake, stress response and virulence factor expression. A better understanding of bacterial communication mechanisms will allow the targeting of quorum sensing with quorum sensing inhibitors to prevent and control disease.